Gambaran Diferensiasi dan Stadium Karsinoma Kolorektal - Welly Hartono Ruslim; Edwin Destra; William Gilbert Satyanegara; Yohanes Firmansyah (Pusat Riset dan Inovasi Nasional, 2023)
Introduction: The third most common type of cancer and the second biggest killer of both men and women is colorectal cancer. Asia and Indonesia are two regions where this carcinoma is an issue. Purpose: To known distribution of gender, primary cancers site, differentiation status, and staging profile of colorectal carcinoma.Method: This research use descriptive observational methods. The Medical Record Tabulation Data of the Faculty of Medicine, UNTAR, from 2020 to 2023 provided the data for this study. Patients with colorectal carcinoma who underwent a routine histological examination met the inclusion criteria for this study. Gender, primary cancer site, differentiation status, and cancer staging profile (TNM classification) were the characteristics evaluated in this study. The statistical method utilized in this study was descriptive analysis. Result: The results of the study revealed that the average age of occurrence of colorectal carcinoma was 58.06 (13.08) years, dominated by male sex in 30 (58.8%) respondents, the most primary location was in the colon at 26 (52.0%) ) respondents, with generally good differentiation in 39 (76.5%) respondents. Conclusion: Colorectal carcinoma most often occurs in the colon and is generally well differentiated.